Application of sodium hypochlorite (NaOCl) for ammonia removal in wastewater effluent of PT. HS - Hiqmatus Sholichah (President University, 2020)
Abstract. PT HS is a world’s leading toy manufacturing company with more than 6,000 workers. Due to the high number of workers in PT. HS, it will impact to domestic activities (toilet discharge). Based on the annual report for wastewater effluent, noted that parameter ammonia from PT HS’s wastewater effluent was exceeding the industrial estate limit which the average of ammonia concentration is 50 mg/L. Whereas, In the industrial estate regulation contain of several standard parameters that must be comply by the company such as ammonia standard which has maximum 10 mg/L for the wastewater effluent. Objectives: The objectives of this experiment are to know the optimum dose of NaOCl 9% on ammonia removal and to know the concentration of residual chlorine after the treatment process. Method and results: This research use the experimental method to get the primary data. After the experiment in the laboratory, the results proved that the sodium hypochlorite exposure reduces ammonia concentration in water samples with 82,2% removal efficiency from 50 mg/L to 8,9 mg/L ammonia concentration reduced with 110 mg/L of NaOCl 9% solution within 30 minutes contact time and it resulted the residual chlorine 0.72 mg/L. Conclusion: The chlorination process was effective to reduce the ammonia concentration. Also, the residual chlorine was still in the standard limit which not exceeds from 1 mg/L. The result also shows that the dose variations of sodium hypochlorite influence ammonia removal efficiencies. Also, mostly the total residual chlorine forecast will increase with the increasing sodium chlorine dose.